2001
DOI: 10.1180/002646101550253
|View full text |Cite
|
Sign up to set email alerts
|

Clinopyroxene-corundum assemblages from alkali basalt and alluvium, eastern Thailand: constraints on the origin of Thai rubies

Abstract: An inclusion of corundum (ruby) was found in a clinopyroxene xenocryst in alkali basalt from the lateCenozoic Chanthaburi-Trat volcanics of eastern Thailand. The clinopyroxene is fairly sodic, highly aluminous and magnesian (0.12 0.14 Na, 0.31 0.33 Al IV and 0.36 0.40 Al VI per 6(O), and Mg/ (Mg+Fe 2+ ) > 0.9)) and is chemically similar to clinopyroxene inclusions in rubies from nearby alluvial gem deposits, suggesting a common origin for the two types of occurrence. Sapphirine (Mg/(Mg+Fe 2+ ) = 0.91 0.94) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 42 publications
10
48
0
Order By: Relevance
“…5) defined for ruby xenocrysts or megacrysts carried up to the surface by alkali basalts . They are also similar to those found for ruby in eclogites derived from oceanic crust (Shirey et al, 2013) and hosted by clinopyroxene xenocrysts from Bo Rai (Thailand) alkali basalt alluvials (Giuliani et al, 2005;Sutthirat et al, 2001; in subducted oceanic crust at relatively high-temperature, i.e. 300-400 8C similar to high-temperature seawater-altered oceanic basalts, the oceanic protolith being subducted to the pressure and temperature regime of the mantle while preserving its lower d 18 O signature (Neal et al, 1990); in mafic protoliths affected by metasomatic percolation of hydrothermal fluids; by metasomatic reactions between pyroxenite or wehrlite intrusions in peridotites such as described for the Beni Bousera plagioclase-rich gabbros (Kornprobst et al, 1990) which contain ruby-bearing garnet pyroxenites (with d 18 O value of ruby = 4.4 %; Table 2).…”
Section: The Cr-bearing Sapphires Of Mbuji-mayimentioning
confidence: 67%
See 1 more Smart Citation
“…5) defined for ruby xenocrysts or megacrysts carried up to the surface by alkali basalts . They are also similar to those found for ruby in eclogites derived from oceanic crust (Shirey et al, 2013) and hosted by clinopyroxene xenocrysts from Bo Rai (Thailand) alkali basalt alluvials (Giuliani et al, 2005;Sutthirat et al, 2001; in subducted oceanic crust at relatively high-temperature, i.e. 300-400 8C similar to high-temperature seawater-altered oceanic basalts, the oceanic protolith being subducted to the pressure and temperature regime of the mantle while preserving its lower d 18 O signature (Neal et al, 1990); in mafic protoliths affected by metasomatic percolation of hydrothermal fluids; by metasomatic reactions between pyroxenite or wehrlite intrusions in peridotites such as described for the Beni Bousera plagioclase-rich gabbros (Kornprobst et al, 1990) which contain ruby-bearing garnet pyroxenites (with d 18 O value of ruby = 4.4 %; Table 2).…”
Section: The Cr-bearing Sapphires Of Mbuji-mayimentioning
confidence: 67%
“…Nevertheless, the associations of corundum together with clinopyroxene and garnet (Sobolev et al, 1998) or Alrich clinopyroxene have been identified in diamond (Hutchinson et al, 2001(Hutchinson et al, , 2004 as well as in corundum (Saminpanya and Sutherland, 2011;Sutherland et al, 2003;Sutthirat et al, 2001). At the Juina kimberlite deposit, high Cr 2 O 3 ruby inclusions in diamond are associated with Al-rich pyroxene (up to 10 wt% Al 2 O 3 ), ferropericlase and Mg-perovskite (Hutchinson et al, 2001).…”
Section: The Rubies Of Mbuji-mayimentioning
confidence: 96%
“…This spinel-sapphirine-ruby facies contrasts with a higher-T, Al-rich diopside-garnet-ruby facies in the Cudgegong-Macquarie River area and a magmatic-related ruby suite in the New England area. It closely resembles a spinel-sapphirine-ruby facies suite from western Palin, Cambodia, even in its oxygen isotope values , but clearly differs from garnet-sapphirineruby suites from a proposed garnet granulite facies in Thailand (Sutthirat et al, 2001).…”
Section: Metamorphic Corundum Sourcesmentioning
confidence: 98%
“…Because many of the mineral assemblages have high variance, it is not generally possible to constrain P-T conditions using the intersection of isopleths of equilibria involving end-member components that are all present in the assemblages concerned; consequently, we have had to rely heavily on the use of equilibria as stability limits, with the activities of absent components set at unity or at partition-corrected values (Sutthirat et al 2001). The P-T coordinates of equilibria were calculated using version 3.1 (2001) of the program THERMOCALC (Powell and Holland 1988;.…”
Section: Metamorphic Conditions and P-t Pathsmentioning
confidence: 99%